Antemortem diagnosis of human rabies: A case report - Wael Goravey (14777254) (2020)
Antemortem diagnosis of rabies is challenging, and usually, more than one test modality is needed to confirm the diagnosis. No effective treatment exists so far, and the Milwaukee Protocol is debatable. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ccr3.3615